Determination of SWCNT biosensor for bisphosphonate–2X(X = Mg2+, Ca2+, Sr2+) delivery in bone cell through electromagnetic and thermodynamic analysis using QM/MC methods - Mollaamin, Fatemeh; Monajjemi, Majid (Emerald, 2024)
Purpose Bisphosphonate (BP) medications can be applied to prohibit the damage of bone density and the remedy of bone illnesses such as osteoporosis. As the metal chelating of phosphonate groups are nearby large with six O atoms possessing the high negative charge, these compounds are active toward producing the chelated complexes through drug design method. BP agents have attracted much attention for the clinical treatment of some skeletal diseases depicted by enhancing of osteoclast-mediated bone resorption. Design/methodology/approach In this work, it has been accomplished the CAM-B3LYP/6–311+G(d, p)/LANL2DZ to estimate the susceptibility of SWCNT for adsorbing alendronate, ibandronate, neridronate and pamidronate chelated to two metal cations of 2Mg2+, 2Ca2+, 2Sr2+ through nuclear magnetic resonance and thermodynamic parameters. Therefore, the data has explained that the feasibility of using SWCNT and BP agents becomes the norm in metal chelating of drug delivery system which has been selected through alendronate → 2X, ibandronate → 2X, neridronate → 2X and pamidronate → 2X (X = Mg2+/Ca2+/Sr2+) complexes. Findings The thermodynamic results have exhibited that the substitution of 2Ca2+ cation by 2Sr2+ cation in the structure of bioactive glasses can be efficient for treating vertebral complex fractures. However, it has been observed the most fluctuation in the Gibbs free energy for BPs → 2Sr2+ at 300 K. Furthermore, Monte Carlo simulation has resulted by increasing the dielectric constant in the aqueous medium can enhance the stability and efficiency of BP drugs for preventing the loss of bone density and treating the osteoporosis. Originality/value According to this research, by incorporation of chelated 2Mg2+, 2Ca2+ and 2Sr2+ cations to BP drugs adsorbed onto (5, 5) armchair SWCNT, the network compaction would increase owing to the larger atomic radius of Sr2+ cation rather than Ca2+ and Mg2+, respectively.